Mthfr as a modifier of the retinal phenotype of Crb1rd8/rd8 mice. (April 2016) - Markand, Shanu; Saul, Alan; Tawfik, Amany; Cui, Xuezhi; Rozen, Rima; Smith, Sylvia B.
Abstract: Mutations in crumb homologue 1 ( CRB1 ) in humans are associated with Leber's congenital amaurosis (LCA) and retinitis pigmentosa (RP). There is no clear genotype–phenotype correlation for human CRB1 mutations in RP and LCA. The high variability in clinical features observed in CRB1 mutations suggests that environmental factors or genetic modifiers influence severity of CRB1 related retinopathies. Retinal degeneration 8 ( rd8 ) is a spontaneous mutation in the Crb1 gene (Crb1 rdr/rd8 ). Crb1 rdr/rd8 mice present with focal disruption in the outer retina manifesting as white spots on fundus examination. Mild retinal dysfunction with decreased b-wave amplitude has been reported in Crb1 rdr/rd8 mice at 18 months. Methylene tetrahydrofolate reductase (MTHFR) is a crucial enzyme of homocysteine metabolism. MTHFR mutations are prevalent in humans and are linked to a broad spectrum of disorders including cardiovascular and neurodegenerative diseases. We recently reported the retinal phenotype in Mthfr -deficient ( Mthfr +/− ) heterozygous mice. At 24 weeks the mice showed decreased RGC function, thinner nerve fiber layer, focal areas of vascular leakage and 20% fewer cells in the ganglion cell layer (GCL). Considering the variability in CRB1 -related retinopathies and the high occurrence of human MTHFR mutations we evaluated whether Mthfr deficiency influences rd8 retinal phenotype. Mthfr heterozygous mice with rd8 mutations (Mthfr +/− rd8/rd8 ) and Crb rd8/rd8 mice (Mthfr +/+rd8/rd8 ) mice were subjected to comprehensive retinal evaluation using ERG, fundoscopy, fluorescein angiography (FA), morphometric and retinal flat mount immunostaining analyses of isolectin-B4 at 8–54 wks. Assessment of retinal function revealed a significant decrease in the a-, b- and c-wave amplitudes in Mthfr +/− rd8/rd8 mice at 52 wks. Fundoscopic evaluation demonstrated the presence of signature rd8 spots in Mthfr +/+rd8/rd8 mice and an increase in the extent of these rd8 spots in Mthfr +/− rd8/rd8 mice at 24 weeks and beyond. FA revealed marked vascular leakage, ischemia and vascular tortuosity in Mthfr +/− rd8/rd8 mice at 24 and 52 weeks. Retinal dysplasia was observed in ∼14–33% Mthfr +/− rd8/rd8 mice by morphometric analysis. This was accompanied by a ∼20% reduction in cells of the GCL of Mthfr +/− rd8/rd8 mice at 24 and 52 weeks. Retinal flat mount immunostaining with isolectin-B4 showed neovascularization and loss of blood vessel integrity in Mthfr +/− rd8/rd8 mice in contrast to mild vasculopathy in Mthfr +/+rd8/rd8 mice. Taken together, our data support an earlier onset and worsened retinal phenotype when Mthfr and rd8 mutations coexist. Our study sets the stage for future studies to investigate the role of MTHFR deficiency in human CRB1 retinopathies. Highlights: The rd8 mouse is a model of Crb-1 mutation. Crb-1 mutations are associated with LCA and RP in humans. Mutations of MTHFR, a homocysteine metabolic enzyme, are prevalent in humans. We investigated the possibility that Mthfr deficiency modifies retinal phenotype in (Crb1) rd8 mice. Mthfr deficiency altered retinal function, morphology and vasculature in rd8 mice. Our data suggest that Mthfr deficiency may be a modifier in Crb-1 related retinopathies.